The Case for The Exclusion of Exclusion: Intellectual Property, Masculine Legal Reason, And the Ethics of Care - Shoukry, Ragya (AUC Knowledge Fountain, 2026)
This thesis argues that current legal ideals of objectivity and neutrality are historically gendered and inseparable from the development of capitalist property relations and imperial expansion. It traces origins that begin with early modern witch hunts and Francis Bacon’s empiricism, where a new “scientific rationality” emerges alongside intensified patriarchal violence. The thesis then examines John Locke’s labour-based justification of property and the figure of the rational individual, showing how this framework legitimizes enclosure, dispossession and colonial appropriation under the guise of improvement and development. Building on this foundation, the analysis turns to moral psychology and how its allegedly universal stage theories are constructed from male, Western subjects and systemically devalue care-centered moral reasoning that Carol Gilligan and feminist scholars bring into view and how it affects legal reasoning’s portrayal as impartial, abstract and objective. Following which the thesis explores how these epistemic and moral frameworks crystallize in legal doctrines governing land, labour, and intellectual property, focusing in particular on intellectual property as a legal infrastructure for capital that privileges exclusion, ownership, and accumulation. As a result, the final chapter develops an ethics‑of‑care approach to creativity, drawing on Gilligan’s ethics-of-care framework along with Boyle, Vaidhyanathan, and Silbey’s contributions and critiques of intellectual property. Rather than proposing a new technical fix within intellectual property law, the thesis argues for a reorientation of the principles through which creative production is understood and organized, toward relational responsibility, stewardship, and a care‑based ecology of creativity.